Surgical Corner of the Mouth Lift – Case Study (Journal of Face Aesthetics, 2023)
A smile is an expression of joy and sympathy, serving as a vital element of social communication. The process of aging has a notable impact on both skin elasticity and muscle tone, which consequently results in alterations in the appearance of the corners of the mouth and the overall smile. Notably, the emergence of 'marionette lines,' vertical wrinkles extending from the mouth's corners to the base of the chin, signifies a visible manifestation of the aging process. These changes exert influence on both aesthetic aspects and personal hygiene, potentially leading to the development of inflammatory conditions.This article presents a case study focusing on a female patient who underwent surgical correction of the mouth's corners due to recurrent angular cheilitis. The patient presented with ptotic mouth corners, excessive salivation, and erythema at the angles of the mouth, often accompanied by painful discomfort during exacerbations of the inflammatory condition. The treatment method applied in this specific case involved the utilization of the triangular technique. Subsequent to the surgical procedure, the patient expressed satisfaction with the outcome, and her mouth corners remained free from inflammatory episodes for a duration of two years.
Keywords: drooping mouth corner; cheilitis angularis; aesthetics; surgical correction of mouth corners using the triangle method